Opportunities and Challenges for Nanotherapeutics for the Aging Population - Hunt, Nicholas J.; McCourt, Peter A. G.; Kuncic, Zdenka; Le Couteur, David G.; Cogger, Victoria C. (Frontiers in Nanotechnology, 2022)
Nanotherapeutics utilize the properties of nanomaterials to alter the pharmacology of the drugs and therapies being transported, leading to changes in their biological disposition (absorption, distribution, cellular uptake, metabolism and elimination) and ultimately, their pharmacological effect. This provides an opportunity to optimize the pharmacology of drugs, particularly for those that are dependent on hepatic action. Old age is associated with changes in many pharmacokinetic processes which tend to impair drug efficacy and increase risk of toxicity. While these age-related changes are drug-specific they could be directly addressed using nanotechnology and precision targeting. The benefits of nanotherapeutics needs to be balanced against toxicity, with future use in humans dependent upon the gathering of information about the clearance and long-term safety of nanomaterials.